About the Vietnamese compound nouns - Thi Hoang Anh Bui (2016)
In an analytic language like vietnamese, according to the position in the utterance, it is relatively easy to recognize the word category of a simple word which can behave as a noun, as a verb, as a particle or as an adverb (Thompson (1965), Nguyen (1997), Cao (2007), Diep (2011), Do-Hurinville (2013)…). But a compound word has not this characteristic as the following questions are complex to be answered : how to determine the boundary of a compound word in the utterance especially if it is formed by more than two components ? How to distinguish a compound noun from a noun phrase (NP), a compound noun from a compound verb ? Are there any grammatical rules to create this type of word? Which criteria to determine whether a composition of two verbs reveals a compound noun or a serial verb construction? Etc. Therefore, our paper aims to propose an inventory of vietnamese compound nouns (henceforth CN). The study will examine the nature of the relationships between the different components of a CN in order to determine if we can distinguish specific patterns proper to each type (if it depends on the type of the elements invoved or on the semantics of the CN). We define a CN as an singular unit composed by two elements or more (each of which can be a noun, a verb or a pronoun) and this unit functions as a single noun in a noun NP. From this point of view, a CN has the same distribution than a single noun in a NP [Quantification – NOUN/ CN – Qualification] Based on syntactic, distributive and semantic criterions, we identify two types of vietnamese CN. In each type, there are different subtypes (cf. (1)-(11)) :-(A) those formed by two heterogenous nouns N 1 N 2 : their semantics construes a collection. We will show that in this type, the notion of 'pluralisation' comes into matter on different plans (cf. (a 1) – (a 4))-and (B) those expressing a predicative relation between their elements (cf. (b 1) – (b 2)) Corpus: a1. N 1 N 2 : N 2 is a complementary of N 1 on semantic plan: (1) ông-bà 'grand-father + grand-mother'-grand-parents' (2) bố-mẹ 'father + mother-parents' a2. N 1 and N 2 share a commun property (3) bàn-ghế 'table + chair-fourniture' a3. N 2 is a chinese or another language borrowed (4) núi-non 'mountain + mountain-moutains' a4. N 1 is a generic term while N 2 is its sub-type. (5) bút-chì 'pen-mine-pencil' b1. X 1 X 2 (6) xe-kéo 'vehicle + pull-pushchair' (7) người-ở 'person + live-servant' (8) thắt-lưng 'tie + back-belt' (9) tri-thức 'know + know-knowledge' b2. Pronoun +X 1 + X 2 + … + X n (10) người-đưa-thư 'person + give + letter-factor' (11) kẻ-ăn-mày 'personne + eat + friend-beggar'